Ageing of composites - Martin, Rod, Dr (Woodhead Publishing in materials., 2008)
Ageing of composites is a highly topical subject given the increasing use of composites in structural applications in many industries. Ageing of composites addresses many of the uncertainties about the long-term performance of composites and how they age under conditions encountered in service. The first part of the book reviews processes and modelling of composite ageing including physical and chemical ageing of polymeric composites, ageing of glass-ceramic matrix composites, chemical ageing mechanisms, stress corrosion cracking, thermo-oxidative ageing, spectroscopy of ageing composites, modelling physical and accelerated ageing and ageing of silicon carbide composites. Part two examines ageing of composites in transport applications including aircraft, vehicles and ships. Part three reviews ageing of composites in non-transport applications such as implants in medical devices, oil and gas refining, construction, chemical processing and underwater applications. With its distinguished editor and international team of contributors, Ageing of composites is a valuable reference guide for composite manufacturers and developers. It also serves as a source of information for material scientists, designers and engineers in industries that use composites, including transport, chemical processing and medical engineering. Addresses many of the uncertainties about the long-term performance of composites and how they age under conditions encountered in serviceReviews processes and modelling of composite ageing including chemical ageing mechanisms and stress corrosion crackingDiscusses ageing of composites in both transport and non-transport applications ranging from aircraft to implants in medical devices.